2019
DOI: 10.36525/sanitas.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Storage Temperature On The Quality Of Honey

Abstract: Honey is natural liquid produced by honey bees. In reality, the quality can be reduced if the storage is not done properly. Diastase enzyme activity is one of the important honey quality parameters. The purpose of this research was to determine the quality of honey that was influenced by storage temperature on the activity of the diastase enzyme using Spectrophotometry method. Samples were obtained from the beekeeping area of East Jakarta. The results showed that, storage temperature greatly affects the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Such samples solely consist of sugars without the presence of the diastase enzyme. Furthermore, Tulandi (2019) showed that storage temperature greatly affected the quality of honey. There was a significant difference in diastase enzyme activity in each treatment at storage temperature.…”
Section: Diastase Enzyme Activitymentioning
confidence: 99%
“…Such samples solely consist of sugars without the presence of the diastase enzyme. Furthermore, Tulandi (2019) showed that storage temperature greatly affected the quality of honey. There was a significant difference in diastase enzyme activity in each treatment at storage temperature.…”
Section: Diastase Enzyme Activitymentioning
confidence: 99%
“…This is because it has been identified that the quality of honey can be altered if stored in inappropriate conditions or if microorganisms gain entry into the honey. [24,25] It was found that the quality of honey reduced if it was stored in extreme conditions, either too hot or too cold temperatures; and a study on "the effect of storage temperature on the quality of honey" revealed that the ideal temperatures for honey storage is room temperature (260 centigrade). Fifty degrees centigrade and ±5 degrees centigrade were not suitable for its storage.…”
Section: Third Stage Of Kolb's Experiential Learning Theory: Abstract...mentioning
confidence: 99%
“…Fifty degrees centigrade and ±5 degrees centigrade were not suitable for its storage. [24] Literature revealed that vinegar use contributed a great deal in the healing of the wound which was found to be colonized by pseudomonas aeruginosa, including chronic wounds such as diabetic wounds, with the recommended concentration being 1%. [16,26] They realized that it would be beneficial to establish protocol for both honey and vinegar use that clearly instruct the amount to be used and expected duration so that all healthcare providers can use them accordingly.…”
Section: Third Stage Of Kolb's Experiential Learning Theory: Abstract...mentioning
confidence: 99%
“…Setelah pendinginan menggunakan vacuum cooling, nilai DN madu karet menurun menjadi 7,98 ± 0,327. Hal ini menunjukkan bahwa adanya penurunan nilai DN setelah dipasteurisasi dan didinginkan disebabkan karena enzim diastase dipengaruhi oleh temperatur; temperatur tinggi dapat menyebabkan kerusakan pada enzim diastase (Tulandi, 2019). Namun, penelitian Andriani (2021) menunjukkan bahwa hasil pasteurisasi menggunakan metode ohmic heating dapat menjaga sifat fisik dan kimia pada madu sialang, yaitu menjaga kandungan gula pereduksi serta total enzim diastase dibandingkan metode konvensional.…”
Section: Gambar 4 Hasil Pengukuran Dn Madu Karetunclassified